K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

1 tháng 7 2022

`(-12. 2/7+8/9:7/2-2/7 . 5/18). 7/2`

`=(-12. 2/7+8/9 . 2/7-2/7 . 5/18). 7/2`

`=2/7.(-12+8/9-5/18) . 7/2`

`=-205/18`

11 tháng 1 2024

5/-6+-5/12 +7/18 = -31/36

2/9+-3/10+-7/10 = 2/9+(-3/10+-7/10)=2/9+(-1)=7/9

-11/6 +2/5 +-1/6 =2/5 +(-11/6+-1/6)=2/5 + -2 =-8/5

-5/8+12/7+13/8+2/7 =(-5/8+13/8)+(12/7+2/7)=1+2=3

 

13 tháng 12 2024

    4.[-2(8:4) + 15(-3) - (-12)]

= 4.[-2.2 - 45 + 12]

= 4.[-4 - 45 + 12]

= 4.[-49 + 12]

= 4.[-37]

= - 148

 

13 tháng 12 2024

    3.(25 : 5 - 14 : 2) - 5.(6:2)

= 3.(5 - 7) - 5.3

= 3.(-2) - 15

= - 6 - 15

= -21

 

27 tháng 3 2017

a.1/4

b.-7/144

c.25/21

d.17/7

e.80/63

f.9/7

27 tháng 3 2017

a)1/4

b)-7/144

c)-25/21

d)17/7

e)16/63

f)9/7

29 tháng 6 2015

Ta có: 7/8 : (2/9 - 1/8) + 7/8 : (1/30 - 5/12) = 7/8 : 7/72 + 7/8 : (-23/60)

                                                             = 7/8.(72/7 - 60/23)

                                                             = 7/8 . 1236/161 = 309/46

a: \(=\dfrac{2}{3}+\dfrac{19}{35}=\dfrac{70+57}{105}=\dfrac{127}{105}\)

b: \(=\dfrac{2}{7}+\dfrac{2}{5}=\dfrac{24}{35}\)

c: \(=\dfrac{7}{12}-\dfrac{14}{2}=\dfrac{7-84}{12}=\dfrac{-77}{12}\)

d: \(=\dfrac{-15}{60}-\dfrac{1}{8}=-\dfrac{3}{8}\)

e: \(=-\dfrac{12}{72}+\dfrac{1}{18}=\dfrac{-3}{18}+\dfrac{1}{18}=\dfrac{-2}{18}=\dfrac{-1}{9}\)

25 tháng 3 2018

Tự làm đi, lười thế

25 tháng 3 2018

a) x= 1/4

b) x= -7/144

c) x= 25/6

d) x=17/7

e) x= 80/63

f) x= -45/14

8 tháng 3 2018

A=21/4+(-9/4)

A=3

10 tháng 8 2016

2/3-6/12+1/4 = 5/12 

4/12-18/24+5/2 = 25/12

-5/7*11/9+5/7*4/9 = -5/9

-3/8*13/11-3/8*3/11 = -6/11

23 tháng 5 2024

  \(\dfrac{1}{2}+\dfrac{3}{4}-\left(\dfrac{3}{4}-\dfrac{4}{5}\right)\)

=\(\dfrac{1}{2}+\dfrac{3}{4}-\dfrac{3}{4}+\dfrac{4}{5}\)

=\(\left(\dfrac{1}{2}+\dfrac{4}{5}\right)+\left(\dfrac{3}{4}-\dfrac{3}{4}\right)\) 

=\(\left(\dfrac{5}{10}+\dfrac{8}{10}\right)+0\)

=\(\dfrac{13}{10}\)

23 tháng 5 2024

\(-\dfrac{7}{25}.\dfrac{11}{13}+\left(-\dfrac{7}{25}\right).\dfrac{2}{13}-\dfrac{18}{25}\)

=\(-\dfrac{7}{25}.\cdot\left(\dfrac{11}{13}+\dfrac{2}{13}\right)-\dfrac{18}{25}\) 

=\(-\dfrac{7}{25}.1-\dfrac{18}{25}\) 

=\(-\dfrac{7}{25}-\dfrac{18}{25}\) 

=\(-\dfrac{25}{25}\) = \(-1\)